3D printed pure carbon-based electrodes for zinc-ion hybrid supercapacitor. (October 2022) - Huang, Qilin; Liu, Ximeng; Wang, John
Abstract: Portable electronics and electric vehicles demand for high-performing, safe and low-cost energy storage devices. Recently, zinc-ion hybrid supercapacitors (ZHS) have gained considerable attention, which is due to their excellent electrochemical performance, high safety and low price. Activated carbon (AC) is one of the most commonly used materials for the cathode in ZHS. However, the lack of properly engineered hierarchical porous conducting electrodes for AC cathode has largely restricted the electrochemical performance of assembled ZHS at present. Herein, a hierarchically porous and self-standing carbon framework is developed by extrusion 3D-printing of activated carbon-Pluronic F127 ink, followed by appropriate thermal annealing to fabricate pure carbon-based electrode. Through formulating the 3D printable pastes, the ratio between the AC and F127 is shown to be crucial for affecting the electrochemical performance. The morphology, pore structure, and surface area of the thus-derived carbon cathode materials are investigated in conjunction with the performance of the zinc-ion supercapacitor. The mechanical stability is discovered to be optimized at the solid concentration range of 35%-40%. Within this range, a higher content of AC in the paste gives rise to better electrochemical performance of the zinc-ion supercapacitor, which is 323.79 mF cm −2 at 3.4 mA/cm −2 (0.1 A/g).